On vertex-induced weighted Turán problems - Xu, Z; Jing, Y; Ge, G (Elsevier, 2021)
Recently, Bennett, English and Talanda-Fisher introduced the vertex-induced weighted Turán problem. In this paper, we consider their open Turán problem under sum-edge-weight function and characterize the extremal structure of Kl-free graphs. Based on these results, we propose a generalized version of the Erdős–Stone theorem for weighted graphs under two types of vertex-induced weight functions.